2008
DOI: 10.1016/j.neulet.2007.11.063
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of stimulated dopamine release and hemodynamic response in the brain through electrical stimulation of rat forepaw

Abstract: The subcortical response to peripheral somatosensory stimulation is not well studied. Prior literature suggests that somatosensory stimulation can affect dopaminergic tone. We studied the effects of electrical stimulation near the median nerve on the response to an amphetamine induced increase in synaptic dopamine. We applied the electrical stimulation close to the median nerve 20 minutes after administration of 3mg/kg amphetamine. We used fMRI and microdialysis to measure markers of DA release, together with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 35 publications
3
20
1
Order By: Relevance
“…A negative correlation between BOLD response and GABA, and between VASO-CBV response and GABA was observed as hypothesized, and related findings have been observed previously using fMRI and contrast agent based techniques (Chen et al, 2008;Reese et al, 2002). However, the observed positive correlation between CBFweighted ASL and baseline GABA was contrary to our hypothesis, and to some previously published results of CBF measurements using different approaches (Reese et al, 2002;Roland and Friberg, 1988;Spanaki et al, 1999).…”
Section: Discussioncontrasting
confidence: 69%
“…A negative correlation between BOLD response and GABA, and between VASO-CBV response and GABA was observed as hypothesized, and related findings have been observed previously using fMRI and contrast agent based techniques (Chen et al, 2008;Reese et al, 2002). However, the observed positive correlation between CBFweighted ASL and baseline GABA was contrary to our hypothesis, and to some previously published results of CBF measurements using different approaches (Reese et al, 2002;Roland and Friberg, 1988;Spanaki et al, 1999).…”
Section: Discussioncontrasting
confidence: 69%
“…Since the approach of facilitating basal ganglia feedback loop through peripheral stimulation relies on the self-adjusting mechanism intrinsic to the basal ganglia loop, the adjustment theoretically can be applied to disorder conditions with either excessive DA (such as in addiction) or with deficient DA innervations (such as in PD). Indeed, such a phenomenon of bidirectional adjustment by EFS is supported by combining data present here for the DA deficient condition and the data published in (Chen et al, 2008a; Chen et al, 2008b) for the DA excessive condition. Interestingly, the effect of EFS on the depressed DA condition appeared to last for the duration of EFS in the quinpirole experiment, but was transient in the Parkinsonian experiment (Figure 4).…”
Section: Discussionsupporting
confidence: 86%
“…We previously demonstrated that innocuous EFS (1mA at 2Hz or 100Hz) effectively attenuated excessive DA concentration in the striatum (Chen et al, 2008a; Chen et al, 2008b). The excessive DA condition was induced pharmacologically by D-amphetamine, a robust DA releaser.…”
Section: Introductionmentioning
confidence: 99%
“…However, from the correlations in our study we cannot ascertain the direction of the association; so we cannot determine if the association with D2 receptors reflects DA's modulation of the somatosensory cortex and/or the influence of the somatosensory cortex on striatal D2 receptor availability. Indeed there is ample evidence that the somatosensory cortex influences brain DA activity including striatal DA release (Huttunen et al, 2003;Rossini et al, 1995;Chen et al, 2007). There is also evidence that DA modulates the somatosensory cortex in the human brain (Kuo et al, 2007).…”
Section: Correlation Between D2r and Somatosensory Cortexmentioning
confidence: 99%